Embodied Music Cognition and Mediation Technology - Leman, Marc (Cambridge, MA MIT Press, 2007)
Digital media handles music as encoded physical energy, but humans consider music in terms of beliefs, intentions, interpretations, experiences, evaluations, and significations. In this book, drawing on work in computer science, psychology, brain science, and musicology, Marc Leman proposes an embodied cognition approach to music research that will help bridge this gap. Assuming that the body plays a central role in all musical activities, and basing his approach on a hypothesis about the relationship between musical experience (mind) and sound energy (matter), Leman argues that the human body is a biologically designed mediator that transfers physical energy to a mental level--engaging experiences, values, and intentions--and, reversing the process, transfers mental representation into material form. He suggests that this idea of the body as mediator offers a promising framework for thinking about music mediation technology. Leman proposes that, under certain conditions, the natural mediator (the body) can be extended with artificial technology-based mediators. He explores the necessary conditions and analyzes ways in which they can be studied. Leman outlines his theory of embodied music cognition, introducing a model that describes the relationship between a human subject and its environment, analyzing the coupling of action and perception, and exploring different degrees of the body's engagement with music. He then examines possible applications in two core areas: interaction with music instruments and music search and retrieval in a database or digital library. The embodied music cognition approach, Leman argues, can help us develop tools that integrate artistic expression and contemporary technology.Marc Leman is Research Professor and Head of the Department of Musicology at Ghent University, Belgium.
Keywords: Corporeality; Music philosophy and esthetics